2013
DOI: 10.1371/journal.pone.0068581
|View full text |Cite
|
Sign up to set email alerts
|

The Community Structure of the European Network of Interlocking Directorates 2005–2010

Abstract: The boards of directors at large European companies overlap with each other to a sizable extent both within and across national borders. This could have important economic, political and management consequences. In this work we study in detail the topological structure of the networks that arise from this phenomenon. Using a comprehensive information database, we reconstruct the implicit networks of shared directorates among the top 300 European firms in 2005 and 2010, and suggest a number of novel ways to exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…Well-connected organisations which attend conferences with other well-connected organisations will have higher eigenvector centralities. Eigenvector centrality gives us a sense of the "rank" of the organisation within the network (Heemskerk et al 2013). Betweenness centrality measures the position of a node between different parts of the network, or the degree to which an organisation may act as a "broker" between different events and organisations (Stovel and Shaw 2012).…”
Section: Actors and Relationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Well-connected organisations which attend conferences with other well-connected organisations will have higher eigenvector centralities. Eigenvector centrality gives us a sense of the "rank" of the organisation within the network (Heemskerk et al 2013). Betweenness centrality measures the position of a node between different parts of the network, or the degree to which an organisation may act as a "broker" between different events and organisations (Stovel and Shaw 2012).…”
Section: Actors and Relationsmentioning
confidence: 99%
“…High betweenness means that the organisation attends many events which are also attended by many actors. In order to see if a node is both well-connected within a part of the network and acts as a bridge, or a "broker", between other parts of the network, we can combine two network measures -eigenvector centrality and betweenness centrality (Heemskerk et al 2013). In Table 2 we can see those organisations which have both high eigenvector centralities and high betweenness by their grey shade.…”
Section: Actors and Relationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, an understanding of network communities seems to be highly relevant in order to understand the functioning of corporate governance mechanisms. For example, Heemskerk, Daolio and Tomassini (2013) apply the community detection heuristics to the interlocking directorship network in Europe, finding evidence of homogenization in the corporate governance mechanisms within Europe.…”
Section: 2network Community Detection As a Tool To Measure Lack Of mentioning
confidence: 99%
“…One of us gave an elaborate analysis of the network of interlocking directorates of the major European corporations in (Heemskerk 2013Heemskerk et al 2013). These studies found that despite the general tendency towards less board interlock activity, the European network of interlocking directorates increased its cohesion.…”
Section: Introductionmentioning
confidence: 99%